Pengaruh Model Pembelajaran POE (Predict-Observe-Explain) Berorientasi Chemoentrepreneurship Terhadap Pemahaman Konsep Siswa Pada Materi Larutan Penyangga - Reni Andriani; Muhali Muhali; Citra Ayu Dewi (Universitas Pendidikan Mandalika Mataram, 2019)
Buffer solution is a material that requires a fairly high analysis withan understanding of concepts that must be understood by studentsand requires practice in everyday life. Learning will be moremeaningful and provide a deep understanding to the learner if thelearning is adapted to the characteristics of the subject matter. Oneeffective solution is to apply the learning model POE (Predict-Observe-Explain) oriented Chemoentrepreneurship. The aim of thisresearch was to evaluatethe influence of learning model POE(Predict-Observe-Explain) oriented Chemoentrepreneurship tounderstanding the concept and. This research was conducted inMAN 2 Praya, the population in this research was student of MIAclass XI, sample was taken by using saturated sampling technique.The design of this research is prettes-posttest control group design.The instruments used to measure conceptual understanding weremeasured using objective tests. Hypothesis testing was performed byusing One-Way ANOVA test with SPSS 15.0 for windows. Based onthe results of the study can be concluded that: Application oflearning model of POE (Predict-Observe-Explain) orientedChemoentrepreneurship influence to understanding student concept.This is evidenced by the sig value. of 0.00 < 0.05.